Frescoes of St. George Church in Bochorma (Georgia) - Makarova, Anna L. (Actual Problems of Theory and History of Art, 2025)
The article presents an attempt at iconographic description and stylistic analysis of frescoes in St. George church at Bochorma (Georgia). Its aim is to disclose the individual artistic peculiarity of this monument and to propose some more parallels in order to define its proper place in the development of Georgian art of the late 11th — early 12th cc.